Computer-aided mobile GPS education set - (:unkn) unknown (TEMPUS PUBLICATIONS, 2008)
This paper describes the design of a computer-aided educational mobile GPS (Global Positioning System) set. By means of this set, use of a GPS receiver and GPS connectivity with mobile devices can be taught more effectively. In addition, students can develop related GPS applications supported by mobile technologies like GSM, GPRS or Bluetooth. This mobile education set enables students to send location information via SMS or compare GPS receivers' data in different locations via GPRS etc. This set consists of a GPS module, an antenna, an 8051-based microcontroller, a monitor ROM for embedded applications, a portable computer and an application software that communicates with the hardware. Educational materials prepared by Macromedia Flash and Java Programming Language have been added to the GPS education set in order to design an efficient student-oriented system.
Keywords: GPS; mobile technology; computer aided; communication; education set